THE ETIOLOGY OF PERPETRATOR OF CHILDREN SEXUAL VIOLENCE: A CASE STUDY IN THE PPA UNIT IN THE POLICE STATION OF SUMBAWA REGENCY - Erliana, Yossy Dwi; Sari Abdullah, Elis Suci Prapita (Universitas Mercu Buana Yogyakarta, 2021)
Sexual violence is any verbal and nonverbal action to manipulate another person to make the person engage in unwanted sexual activity. Recently, sexual violence against children in Sumbawa Besar District raised the concerns of various groups. This is due to the increasing number of cases of sexual violence against children. The purpose of this research is to find out causes (the etiology) of the perpetrators in comitting sexual violence. The method used in this research is qualitative research with the case study approach. The data were collected using interview and observation methods. The subjects of this study were perpetrators of sexual violence in Sumbawa district. The data credibility was examined with triangulation of source, technique, and theory. The four stages of data analysis were data collection, data sortation, data conclusions, and data verification. The results showed that there were various reasons of the perpetrators to commit sexual violence towards children. Some of the factors are problems in their families and the need and opportunity to fulfill their sexual desires.